1619. Meta-analysis of Randomized Control Trials Evaluating New Beta-Lactamase Combination Antibiotics. (31st December 2020) - Wilson, Geneva M; Fitzpatrick, Margaret A; Walding, Kyle; Gonzalez, Beverly; Suda, Katie J; Evans, Charlesnika T
Abstract: Background: Ceftolozane/ Tazobactam (C/T), Ceftazidime/ Avibactam (C/A), Meropenem/ Vaborbactam (M/V) and Imipenem/ Relebactam (I/R) are new combination beta-lactam/ beta-lactamase inhibitor antibiotics primarily used to treat multidrug-resistant (MDR) Gram-negative infections. This study synthesized outcomes of comparative observational studies and randomized control trials (RCTs) that evaluated clinical success of these antibiotics compared to other therapies. Methods: PubMed, EMBASE, and Google Scholar were searched from January 1 st, 2013 through October 1 st, 2019 for comparative observational studies and RCTs of C/T, C/A, M/V and I/R in patients with pneumonia, complicated intra-abdominal and urinary tract infections. Study and patient demographics were collected along with clinical and microbiological success rates. Meta-regression analysis was used to determine the pooled effectiveness of C/T, C/A, M/V, and I/R. Heterogeneity and publication bias were assessed via I 2 values and funnel plots, respectively. Results: Literature search returned 1, 645 results. After exclusion criteria, 21 publications representing 6, 246 patients were retained: 16 RCTs (8 C/A, 3 C/T, 3 I/R, 2 M/V) and 5 comparative observational studies (3 C/A, 2 C/T). Pooled risk ratios for clinical success showed that all four antibiotics were non-inferior to comparator antibiotics (0.99 (95% CI (0.97-1.01)). Eleven of the sixteen RCTs evaluated microbiological success; pooled risk ratio was 1.08 (95% CI 1.04-1.13), indicating that older therapies were more successful at microbiological eradication than newer antibiotics. Only 6 of the included studies (3 RCTs and 2 observational studies) focused on patients with MDR infections. Limiting the analysis to MDR RCTs did not change the overall conclusions. Conclusion: Although older therapies had slightly higher microbiologic clearance, pooled clinical success rates for C/A, C/T, M/V, and I/R were non-inferior to older therapies, including in studies focused on patients with MDR infections. Additional studies are needed to further evaluate these drugs' effectiveness for treatment of MDR infections. Disclosures: All Authors : No reported disclosures